1998
DOI: 10.1103/physrevb.58.11676
|View full text |Cite
|
Sign up to set email alerts
|

Current-voltage characteristics of semiconductor-coupled superconducting weak links with large electrode separations

Abstract: We have studied the current-voltage characteristics of superconducting weak links in which the coupling medium is the 2-D electron gas in InAs-based semiconductor quantum wells, with relatively large (typically 0.5µm) separations between niobium electrodes. The devices exhibit Josephson-like current-voltage characteristics; however, the falloff of the differential resistance with decreasing temperature is thermally activated, and is orders of magnitude slower than for more conventional weak links. Most unexpec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
(66 reference statements)
2
14
1
Order By: Relevance
“…iii) The zero-bias differential resistance dV /dI| V =0 increases (and the current decreases) with temperature. These points of qualitative agreement between experiment and theory support the view of Thomas et al that multiple Andreev reflections are responsible for the observed nonequilibrium effects [12]. The characteristic shape of the CVC described in ii) has been also observed for a single SNS junction by Kroemer et al [10].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…iii) The zero-bias differential resistance dV /dI| V =0 increases (and the current decreases) with temperature. These points of qualitative agreement between experiment and theory support the view of Thomas et al that multiple Andreev reflections are responsible for the observed nonequilibrium effects [12]. The characteristic shape of the CVC described in ii) has been also observed for a single SNS junction by Kroemer et al [10].…”
Section: Discussionsupporting
confidence: 84%
“…For the numerical computation of the proximityinduced pair potential and the current-voltage characteristics we use system parameters similar to the ones reported by the Kroemer group [9,10,12]. We assume that the InAs channel extends in x-direction over 15 nm (thickness L x ), and in z-direction the extensions of the insulating layers between the Nb electrodes, 2a, and of the Nb electrodes themselves, D − a, are about 500nm.…”
Section: Proximity Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the single-particle Hamiltonian takes the usual form for the 2D SM in the presence of the spin-orbit Rashba interaction ( = 1):where m * , α and µ are the effective mass, the strength of spin-orbit interaction and chemical potential, respectively. The latter can be controlled using the gate electrodes [11,13]. The last term in Eq.(2) corresponds to the Zeeman term due to the applied external magnetic field aligned along thex-axis, V x = g SM µ B B x /2.…”
mentioning
confidence: 99%
“…The dc characteristics of the gratings have been studied extensively and published elsewhere [8]; in this article we show only dc characteristics of the single junctions. …”
Section: Devices and Experimental Techniquementioning
confidence: 99%